Acquired RAS or EGFR mutations and duration of response to EGFR blockade in colorectal cancer - Beth O. Van Emburgh; Sabrina Arena; Giulia Siravegna; Luca Lazzari; Giovanni Crisafulli; Giorgio Corti; Benedetta Mussolin; Federica Baldi; Michela Buscarino; Alice Bartolini; Emanuele Valtorta; Joana Vidal; et al. (Nature Communications, 2016)
Some colorectal cancer patients respond well to treatment with anti-EGFR antibodies, however response is almost invariably followed by acquired resistance. Here, the authors show that patients with shorter responses acquireRAS mutations, while those relapsing later preferentially develop mutations in the extracellular domain of EGFR.